Gelatin-based spray for forest fire prevention and fertilization - Yuanfang Ai; Na Zheng; Wenbo Liu; Ping Yang; Xi Wu; Yichen Tian; Chuyi Wang; Heyang Liu; Chongping Huang; Zhongli Liang; Feng Zhu; Longcheng Tang; et al. (Communications Materials)
Abstract Frequent forest fires, driven by hotter and drier climates, threaten biodiversity and human health, causing significant economic losses, air pollution, soil erosion, and degeneration. Current active and passive fire protection methods often suffer from environmental pollution, poor flexibility, and limited availability in remote areas. However, fast-acting surface flame retardants for passive forest fire protection, particularly for foliage, are rare. Herein, we report an easily obtainable gelatin-based fire spray, which resulted in 1.8 and 16.3-fold extension in ignition time, 34% and 39% reductions in total heat release, 78% and 92% reductions in fire growth index for dead and fresh leaves, respectively. After the fire warning is suppressed, for instance by rain, the sprayed substances can decompose and provide nitrogen and phosphorus as leaf and soil fertilizers without affecting soil microbial function, which increase plant net photosynthesis by 84% and effective nitrogen and phosphorus by 664% and 140%, respectively. Our green flame retardant and fertilizer material allows for simultaneous tree fire protection and growth.